Amyand's Hernia in a 6-Week-Old Infant: A Delayed Diagnosis - Piedade, C (2013)
In Amyand's hernia, the hernia sac contains the appendix. This can be normal and accidentally found during herniotomy or inflamed and present as acute scrotum, although the latter is less frequent. We present a case of a male infant with scrotal abscess resulting from Amyand's hernia, with appendicitis and periappendicular abscess.